2020
DOI: 10.1186/s12870-020-02763-z
|View full text |Cite
|
Sign up to set email alerts
|

1Selenium supply alters the subcellular distribution and chemical forms of cadmium and the expression of transporter genes involved in cadmium uptake and translocation in winter wheat (Triticum aestivum)

Abstract: Background Cadmium (Cd) accumulation in crops affects the yield and quality of crops and harms human health. The application of selenium (Se) can reduce the absorption and transport of Cd in winter wheat. Results The results showed that increasing Se supply significantly decreased Cd concentration and accumulation in the shoot and root of winter wheat and the root-to-shoot translocation of Cd. Se application increased the root length, surface area and root volume but decreased the average root diameter. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…While all assemblers produced less than 65,000 transcripts for both, di- and autotetraploid A. thaliana , the number of transcripts in the Acer and Vaccinium assemblies was multiple times higher ranging from 134,424 up to around 355,230 in case of the diploids, and from around 280,852 to more than 735,465 in the autotetraploids. That tendency is surprising because the number of genes in some Vaccinium and Acer species is estimated only to be in the range or utmost twice the number of the 27,000 annotated genes in A. thaliana [ 37 , 49 – 51 ]. Of course, one should be aware that this is only an estimation and could be underestimated for Acer and Vaccinium due to the lack of completely sequenced and annotated genomes for those genera [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While all assemblers produced less than 65,000 transcripts for both, di- and autotetraploid A. thaliana , the number of transcripts in the Acer and Vaccinium assemblies was multiple times higher ranging from 134,424 up to around 355,230 in case of the diploids, and from around 280,852 to more than 735,465 in the autotetraploids. That tendency is surprising because the number of genes in some Vaccinium and Acer species is estimated only to be in the range or utmost twice the number of the 27,000 annotated genes in A. thaliana [ 37 , 49 – 51 ]. Of course, one should be aware that this is only an estimation and could be underestimated for Acer and Vaccinium due to the lack of completely sequenced and annotated genomes for those genera [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both species show a similar distribution pattern across Europe and are valuable hardwood species [ 35 , 36 ]. Further, Vaccinium is a young and widespread genus with elevated rates of speciation in recent decades that led to the formation of about 450 species [ 37 ]. The genus includes blueberries, cranberries or lingonberries and consists of very complex polyploid species like Vaccinium corymbosum L., a highly economically relevant species in the food sector [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparatively highest significant ( p < 0.05) effect was noticed upon co-application of Se + Si treatment followed by Se treatment, respectively ( Table 1 ). The increase in plant biomass upon co-application of Se + Si may be attributed to Se-induced plant physiological and enzymatic regulation against Cd-induced oxidative and metabolic damages [ 20 ] and plant morphological adaptations to reduce Cd uptake and structural damages [ 19 ]. Abdalla et al [ 15 ] also revealed a positive impact of Se on water-soluble sugars under S-deficient conditions in Lettuce.…”
Section: Discussionmentioning
confidence: 99%
“…Se/Si treatments also increased grain yield, antioxidant enzyme activities, and reduced MDA in wheat tissues [ 21 ]. Past studies reported that Se applications were more effective than Si on plant physiological growth under Cd stress [ 16 , 20 ]. In contrast, our study indicated significant p < 0.05 plant physiological growth with Si and Si + Se treatments under Cd stress.…”
Section: Discussionmentioning
confidence: 99%